PENGARUH JENIS DAN WAKTU PEMBERIAN BOKASHI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays L. saccharata Sturt) VARIETAS SUPER SWEET - Wike Setiani (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
Effect of Type and Bokashi Application Time on the Growth and Yield of Sweet Corn (Zea mays L. saccharata Sturt), Super Sweet variety. Objectives of the research were to know the effect of Bokashi types and application time as well as their interactions on the growth and yield of sweet maize.  The research lasted for about four months, started from February 2013 to May 2013, carried out in Dempar Village,  Nyuatan Sub-District of West Kutai District, East Kalimantan Province.  The research employed Randomised Block Design (RBD) with factorial 3x3 experiment and 3 replications.  The first factor was Bokashi fertilizer types (A), that consisted of three levels, namely: no bokashi fertilizer (a1), bokashi of paddy straw (a2) and bokashi of reeds (a3).  The second factor was Application Time of Bokashi (B), that consisted of three levels, namely: bokashi was given 1 week before planting (b1), given 2 weeks before planting (b2), and given 3 weeks before planting (b3).  Results of the research indicated that Bokashi fertilizer types (A)  affect significantly on plant height at 15 days after planting, but it did not affect significantly on plant height at 35 days and 45 days after planting, male flowers appear, cob length, cob diameter, cob weight, and cob production.  Application time of bokashi (B) did not affect significantly on plant height at15 days,  35 days, and 45 days after planting, male flowers appear, cob length, cob diameter, cob weight, and cob production.  The interaction between bokashi fertilizer types and application time of bokashi did not affect significantly on plant height at 35 days 15 days 45 days after planting, flowers males appear, cob length, cob diameter, cob weight  and cob production.